Characterization of CD4+ Lymphocyte From Bone Marrow Stem Cell Using Indirect Immunofluoresence For HIV & AIDS Treatment - Purwati Purwati (Stem Cell Research and Development Center, Universitas Airlangga, 2021)
Acquired immune deficiency syndrome (AIDS) is caused by Human Immunodeficiency Virus (HN). At the beginning of infection, gpl20 virus interacts with CD4 receptor at the surface of the target cell. The interaction between gpI20 and CD4 leads to the occurrence of the binding of specific chemokine receptor CXCR4 and CCR5, which are also present on the membrane of the target cell. Therefore, CCR5 arid CXCR4 also determine the fate of the target cell. It is the performance of CCR5 and CXCR4, guided by controlling gene that determines susceptibility or resistance to HN infection. Coding gene CCR5 may mutate to become protective or resistant against HTV infection. In homozygote individuals, it tends to be resistant against infection while in heterozygote individuals it tends to be susceptible to HN infection. Objective: To characterize TCD4 lymphocyte in the next that is resistant against HN infection by using gene therapy deletion 32 CCR5 to use for HTV & AIDS treatment. Method: Sample collection, mononucleated cell collection, lymphocyte culture, CD4 identification, CCR5 variance analysis, co-cultivation with PBMC HN and comparison to control. Result: This study was performed in several steps, such as mononucleated cell isolation, followed with cell culture, lymphocyte purification, lymphocyte and CD4 expression identification. Conclusion: Lymphocyte T CD4 had been mature after seven passages, once passage is about 5 days so for maturity lymphocyte T CD4 need 35 days and that cell as be candidate to resistant against HN infection by using gene therapy deletion 32 CCR5 to use for HN & AIDS treatment.